(untitled) (Anwer Khan Modern Medical College Journal, 2022)
Background and objectives: AKI is an increasingly common complication of critical illness, with some researches showing that as high as 1 in 5 adults and 1 in 3 children experiencing AKI per hospital admission. Whether occurring in the community or in the hospital, the clinical and public health importance of AKI is well established due to the association with high mortality and its separate independent effect on the risk of death and resource use. This study was aimed to find out the etiology and outcome of acute kidney injury patients requiring haemodialysis. Methods: A retrospective study was done on 70 patients of AKI who required haemodialysis support in dialysis unit of medicine department of Jahurul Islam Medical College Hospital, Kishoreganj during the time period from Jan - 2018 to Dec – 2020. All patients of age 13 and above with AKI and have been dialyzed at least once during the study period were included. Results: In this study, there was an overall male preponderance (70%) with age range of 13-40 years (48.57%). Most common features of presentation were oliguria, cough, respiratory distress, drowsiness, disorientation, reddish urine, pedal edema, fever and high blood pressure. The most common causes of AKI were sepsis (30%), hypovolemia (21.42%), acute glomerulonephritis (AGN) (14.29%) and pregnancy related causes (10%). Common indications for haemodialysis of AKI patients were refractory fluid overload (70%), features of uraemic encephalopathy (22.86%). In this study, 78.57% of AKI patients requiring haemodialysis were improved and discharged, 08.57% patients were progressed to end stage renal disease, 07.15% patients were expired and 05.71% patients were absconded. Conclusion: It is concluded that sepsis, hypovolemia, AGN, obstetric causes, surgical causes and nephrotoxins were the primary causes of AKI patients requiring haemodialysis in this study. Most of these causes can be prevented with simple interventions such as appropriate management of infections, health education on oral rehydration, quality prenatal and emergency obstetric care and taking appropriate precautions when prescribing potentially nephrotoxic medications. Majority of the patients of AKI with complications were improved with haemodialysis. So, expansion of haemodialysis services to all parts of the country is necessary. AKMMC J 2021; 12(2): 98-103